56‐2: Thin Foldable AMOLED Module with Excellent Low‐Temperature‐Bendability and Pencil Hardness. Issue 1 (25th September 2020) - Murao, Takehiro; Kikuchi, Ryo; Tsuchida, Kenichiro; Togashi, Yasuyuki; Sakai, Akira; Hasegawa, Masahiro; Yamada, Miho; Watanabe, Noriko; Yasuda, Yuki; Smeeton, Tim M.; Boardman, Edward A.
Abstract : We explored the effect of thickness and slip property of OCA and developed simulations which succeeded perfectly in reproducing OCA behavior at both room and low temperature. Finally, we developed foldable OLED modules with excellent low‐temperature bendability and pencil hardness. We also mentioned thin coating polarizer for the future products.